PREDICTIVE POLICING: THE FUTURE OF CRIME PREVENTION CASE STUDY OF CHILDREN BRAWL IN THE JURISDICTION OF THE SOUTH JAKARTA METRO POLICE - Daniel Dirgala; Basir S.; Surya Nita (Lafadz Jaya Publisher, 2023)
This study aims to describe brawls that occur in the jurisdiction of the South Jakarta Metro Police, identify correlations that are the factors that influence the prevention of brawls in the jurisdiction of the South Jakarta Metro Police, reveal the practice of preventing child brawl crimes through the implementation of predictive policing that occurs in the jurisdiction of the South Jakarta Metro Police. This research is descriptive qualitative using a case study research type. The findings revealed that brawls occurred under the jurisdiction of the South Jakarta Metro Police from 2019 to 2021, indicating that attempts to avoid brawls by the South Jakarta Metro Police have had minimal effect because there has been an increase every year and can only prevent 7 acts of brawl. Factors that have caused the prevention of brawls in the jurisdiction of the South Jakarta Metro Police to be less effective because they have weaknesses and threats/obstacles they face. Concerning the weaknesses, there are aspects of the quantity of human resources, aspects of the quantity of facilities, and aspects of work methods at Satbinmas (Community Development Unit) and Satsamapta South Jakarta Metro Police, which carry out preemptive (door to door system patrol activities, and FGD) and preventive (walking patrols, motorized patrols, and monitoring through CCTV), while the aspect of a lack of budget is for Satbinmas, which carry out pre-emptive (door to door system patrol activities, and FGD).